'HEAVEN HELP THE YANKEES IF THEY CAPTURE YOU': WOMEN READING GONE WITH THE WIND IN OCCUPIED GERMANY. (12th March 2018) - Oliver, Emily
ABSTRACT: First published in German in 1937, Margaret Mitchell's Gone with the Wind was one of the most popular books in Germany throughout the Second World War and well into the occupation period. This article investigates why Mitchell's tale of the American Civil War and the South's humiliating defeat and subsequent occupation by hostile powers captured the popular imagination in occupied Germany. Drawing on the portrayal of women in the post‐war German press, the article illuminates how Scarlett O'Hara's transgression of traditional gender roles offered female readers potential for identification with the central character. Through reading Gone with the Wind in relation to debates about women's behaviour, relationships, and bodies during the occupation period, it argues that the novel participated in the victim discourse arising within Germany immediately after the Second World War.